Clinical development, registration, and introduction of human rotavirus vaccine: The Latin American experience - Schael, Irene Perez (2012)
Rotavirus (RV) is the leading cause of severe gastroenteritis (GE) among infants and young children worldwide, accounting for 453,000 deaths in children aged <5 years. In Latin America rotavirus causes an estimated 15,000 deaths annually and accounts for 20–70% of acute gastroenteritis cases requiring hospitalization. This results in an estimated annual cost of approximately US$86 million. The most common G type has been G1 (∼50%), followed by G4, G3 and G9, although regional and temporal variations are significant. There are currently two effective rotavirus vaccines: a single-strain, human attenuated-based (RotarixTM, GlaxoSmithKline Biologicals), and a five-strain, bovine-human reassortant vaccine (RotaTeqTM, Merck and Company). The pioneering strategy behind the development and licensure of RotarixTM was part of a new paradigm for global vaccine research and development focusing on introduction first in countries with greatest medical needs. Rotarix™ demonstrated high efficacy and a good safety profile in Phase II and III clinical trials performed in Latin America. In the pivotal phase III study involving 11 Latin American countries a 2-year efficacy of 81% (95% CI: 71–87) was achieved against severe rotavirus acute gastroenteritis. A high protective efficacy was observed against severe rotavirus gastroenteritis caused by G1 and non-G1 strains. RotarixTM proved to be safe regarding intussusception (IS) in a two-dose vaccine schedule beginning at 6–12 weeks of age. First registered in Mexico in July 2004, Rotarix™ gained World Health Organization (WHO) prequalification in February 2007 and has been introduced for routine use into the universal mass vaccination programs of Brazil, Panama, Mexico, Venezuela, Ecuador, Guatemala, Honduras, Colombia, Paraguay, Bolivia, Peru, and El Salvador. The main factors influencing the decision-making process of introducing rotavirus vaccines in Latin American countries included: (a) demonstration of good efficacy/safety profiles; (b) political decision to decrease mortality; (c) decision from ministries of health; (d) availability of data on the disease burden; (e) cold chain available; and, importantly (f) the use of PAHO's Revolving Fund for the purchase of vaccines. Post-licensure studies have shown 76% (95% CI: 64–84%) effectiveness in El Salvadoran children and 76% (95% CI: 58–86%) to 85% (95% CI: 53–94%) in Brazil. Observational studies in Panama, Mexico, El Salvador and Brazil reported reduction in all-cause diarrhea-related hospitalizations at rates of 22–37%, 11–40%, 35–48%, and 17–48%, respectively. The decline in diarrhea-associated deaths reached 35% (95% CI: 29–39%) in Mexico and ranged from 22% (95% CI: 6–45%) to 33% (95% CI: 15–52%) among Brazilian children. A low, increased risk of intussusception was detected among Mexican infants within 7 days after first vaccine dose [odds ratio, 5.8 (95% CI: 2.6–13)]. Continuous and expanding post-licensure rotavirus surveillance studies are needed to better assess the effect of universal vaccination in Latin American countries and elsewhere.